Long-Run and Short-Run Effects of Trade Openness on Life Quality in Sub-Saharan Africa - Nkemgha, Guivis Zeufack; Mbita, Aimée Viviane; Mve, Symphorin Engone; Tchoffo, Rodrigue (Asian Journal of Empirical Research, 2021)
This paper contributes to the understanding of the other neglected effects of trade openness by analysing how it affects life quality in sub-Saharan African countries over the period 2000–2016. We used two trade openness indicators, namely: Squalli and Wilson index and the rate of trade. The empirical evidence is based on a pooled mean group approach. With two panels differentiated by their colonial origin, the following findings are established: the trade openness variable measured by Squalli and Wilson index has no effect on life quality in the both groups of countries in the short-run. However, it has a positive and significant effect on life quality in the both group of countries in the long-run. The use of the rate of trade confirms the results in the both groups of countries in the long-run. The contribution of trade openness to life quality is 3.27 and 5.19 times higher in the Former British Colonies than that recorded in the Former French Colonies of SSA respectively to the use of Squalli and Wilson index and the rate of trade. Overall, we find strong evidence supporting the view that trade openness promotes life quality in SSA countries in the long run.